Brigatinib-repurposed chemo-photodynamic therapy nanoplatform via effective apoptosis against colorectal cancer. (February 2023) - Su, Miao; Tian, Hailong; Zhou, Li; Li, Qiong; Wang, Shuqi; Haung, Canhua; Nice, Edouard C.; Zheng, Shaojiang; Li, Jingquan
Graphical abstract: A repurposed chemo-photodynamic therapy nanoplatform, capable of manipulating redox homeostasis and enhancing endoplasmic reticulum stress, was designed for augmented colorectal cancer suppression by integrating the brigatinib and Ce6. Highlights: We rationally designed a repurposed chemo-photodynamic therapy nanoplatform (BCT NPs) capable of manipulating redox homeostasis and boosting ER stress against CRC by combining the chemotherapeutic agent brigatinib with photosensitizer Ce6 into a TPGS-based nanosystem. BCT NPs can significantly improve their bioavailability by enhancing the dispersibility of brigatinib and Ce6 in aqueous solution and are suitable for intravenous administration, greatly reducing the dosage and toxic side effects. BCT NPs with uniform and suitable sizes can effectively deliver the photosensitizers Ce6 and brigatinib to tumor tissue through the EPR effect. Brigatinib in BCT NPs induces cell apoptosis by triggering ER stress; Ce6 generates a large amount of singlet oxygen, induces cellular oxidative stress, and synergistically promotes tumor cell apoptosis. Abstract: Colorectal cancer (CRC), a malignancy with a relatively high fatality rate, still poses a growing global public health challenge due to the lack of well-established and effective treatment strategies. Brigatinib, an ALK inhibitor approved for the treatment of ALK-positive NSCLC, has been repurposed to suppress the growth of ALK-negative CRC cells via sustained endoplasmic reticulum (ER) stress. Moreover, the photosensitizer Chlorine e6 (Ce6) exhibits a high singlet oxygen quantum yield, which promote the generation of reactive oxygen species (ROS) to exacerbate ER stress and function synergistically with chemotherapeutics. However, the clinical application of both brigatinib and Ce6 is limited by their poor water solubility. Therefore, a repurposed chemo-photodynamic therapy nanoplatform (BCT NPs) utilizing d-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) as a nanocarrier for the codelivery of the chemotherapeutics brigatinib and photosensitizer Ce6 is developed, which is capable of disrupting redox homeostasis and enhancing ER stress against CRC. The developed nanoplatform successfully addressed therapeutic drug solubility, improved brigatinib biocompatibility with a lower hemolysis rate, and demonstrated satisfactory CRC suppression effects in vitro and in vivo . Overall, BCT NPs provide a promising strategy to construct repurposed and versatile nanoplatforms against CRC.